Analisis Lingkungan Rumah Sakit Umum Bethesda Serukam Kalimantan Barat sebagai Dasar Pemilihan Strategi dalam Menghadapi Sistem Jaminan Sosial Nasional - Marksriri, Theresia Tatie; Trisnantoro, Laksono; Andayani, Niluh P E (Jurnal Kebijakan Kesehatan Indonesia, 2018)
Background: Universal Health Coverage known as Jaminan Kesehatan Nasional (JKN) started at 1st January 2014 managed by the Social Security Administrative Bodies (BPJS). Bethesda General Hospital is a class C hospital that located in Bengkayang Regency, West Borneo. This hospital does not have any strategic plan which requires an analysis to map the issues needed to join in JKN system. The analysis can become a recommendation for the hospital strategic plan. Objective: To describe the analysis of the health insurance for patient service unit in the hospital and giving a recommendation for the hospital strategic planning. Method: The study design is a case study with a single-case embedded design. The informant are Head Regency, Health Office, Hospital Directors of other hospital, Bethesda General Hospital worker, Bethesda Serukam Foundation and World Venture Mission. The data taken from observation, in-depth interview, FGD and secondary data. Result: The hospital has the opportunities that come from government support, cooperation with other surrounding hospital which helped the hospital to gain a good reputation and many patients with UHC. The threats are the unclear of UHC socialization, and market competition with other surrounding hospitals and hospital tendency to accept severe diagnosis. The hospital strengths are equity service in organization culture, teamwork and support from mission/donor. The weaknesses are lack of quality and budget control, no clinical pathway, the health information system is not running well, lack of human resources and competence, also unclear organization structure. Conclusion and recommendation: The SWOT resulted from hospital environment helps to formulate the strategy toward universal health coverage. The general strategic suggested is the growth strategy in healthcare services. Latar belakang: Sistem Jaminan Sosial Nasional mulai diselenggarakan oleh Badan Penyelenggara Jaminan Sosial (BPJS), sejak 01 Januari 2014. RSU Bethesda Serukam adalah RS kelas C, terletak di Kabupaten Bengkayang, Kalimantan Barat. RSUB belum memiliki rencana strategis. Dibutuhkan suatu analisis lingkungan yang dapat memetakan isu-isu yang akan dihadapi RS dalam menyambut era BPJS. Tujuan: Mendeskripsikan dan menganalisis situasi lingkungan unit pelayanan pasien Askes dan Jamkesmas RSUBS, serta memberikan rekomendasi strategi untuk penyusunan rencana strategi. Metode: Jenis penelitian adalah studi kasus dengan desain kasus tunggal terjalin. Responden penelitian adalah Bupati Bengkayang, Kepala Dinas Kesehatan Kabupaten Bengkayang, Direktur RS sekitar RSUBS, pejabat struktural dan fungsional RSUBS, perwakilan Yayasan Bethesda dan misi World Venture. Sumber data dari observasi, wawancara mendalam dan pedoman diskusi kelompok terarah serta data sekunder rumah sakit. Hasil dan pembahasan: Peluang RSUBS adalah dukungan pemerintah kabupaten, kerjasama dengan RS sekitar, nama RS yang sudah dikenal baik dan banyak pasien berobat dengan JKN. Ancamannya adalah sosialisasi pelayanan JKN yang belum jelas, serta persaingan dengan RS sekitar serta kecenderungan RS menerima pasien sulit. Kekuatan RSUBS adalah budaya RS yang tidak membeda-bedakan pelayanan, kerjasama tim dan dukungan donatur misi. Kelemahannya adalah kurangnya kendali mutu dan biaya, belum ada clinical pathway, SIRS belum berjalan baik, kurangnya SDM dan struktur organisasi yang tidak jelas. Kesimpulan dan saran: Analisis lingkungan rumah sakit menghasilkan kekuatan, kelemahan, peluang dan ancaman untuk formulasi strategi dalam menghadapi SJSN. Strategi umum yang tepat untuk RSUBS dalam menghadapi perubahan SJSN adalah strategi pertumbuhan dalam kegiatan pelayanan kesehatan.